A LIFE WITHOUT TRANSLATION: ARIEL DORFMAN AND HIS DOUBLE LIFE - Brisolara, Valeria (Revista (Entre Parênteses), 2020)
This article aims at presenting and relating the essay “Footnotes to a double life” and the memory narratives Heading south, looking north: a bilingual journey and Rumbo al sur, Deseando el norte: un romance en dos lenguas, using them as a starting point for a discussion on translation, linguistic mobility (BRISOLARA, 2010), and language memories (PAVLENKO, 2006). The main issue, in the perspective adopted, and that has guided our studies, focused on the construction or reconstruction of authorship, of an authorial voice, at the merger of these two languages. (BRISOLARA, 2017).